History of Land Tax: Old Tax Documents as a Reference for Land Registration and the Mechanism for Recording in the Letter C Book - I Gede Yudi Arsawan; Ardani, Ni Ketut (Focus Journal : Law Review, 2025)
This article explores the historical role of old tax documents, particularly the Letter C Book, as crucial references in land registration processes in Indonesia. The background highlights the legal challenges in proving land ownership in areas where formal certificates are absent, emphasizing the significance of Letter C as a traditional land record maintained by village authorities. Using a normative legal research method, the study analyzes regulations and historical practices governing the use and recording of Letter C documents, focusing on their reliability and legal standing amid evolving land registration laws. The research finds that while old tax documents provide strong indications of land rights, the absence of formal certification necessitates urgent registration to secure legal ownership. Furthermore, the study identifies risks of forgery due to inconsistent record-keeping and recommends procedural reforms for validating Letter C entries. Ultimately, the article concludes that integrating old tax documents into formal land registration is essential for legal certainty and land tenure security.